Elaidic acid-induced intestinal barrier damage led to gut-liver axis derangement and triggered NLRP3 inflammasome in the liver of SD rats - Hui Liu; Xuenan Li; Lu Li; Yucai Li; Haiyang Yan; Yong Pang; Wenliang Li; Yuan Yuan (Food Science and Human Wellness)
Previous studies have shown that trans fatty acids (TFA) are associated with several chronic diseases, the gut microbiota is directly influenced by dietary components and linked to chronic diseases. Our research investigated the effects of elaidic acid (EA), a typical TFA, on the gut microbiota to understand the underlying mechanisms of TFA-related chronic diseases. 16S rDNA gene sequencing on faecal samples from Sprague-Dawley rats were performed to explore the composition change of the gut microbiota by EA gavage for 4 weeks. The results showed that the intake of EA increased the abundance of well-documented harmful bacteria, such as Proteobacteria, Anaerotruncus, Oscillibacter and Desulfovibrionaceae. Plus, EA induced translocation of lipopolysaccharides (LPS) and the above pathogenic bacteria, disrupted the intestinal barrier, led to gut-liver axis derangement and TLR4 pathway activation in the liver. Overall, EA induced intestinal barrier damage and regulated TLR4-MyD88-NF-κB/MAPK pathways in the liver of SD rats, leading to the activation of NLRP3 inflammasome and inflammatory liver damage.